Demographic Changes and Human Security of Syrian Refugees - Shamieh, Luna (Magyar Rendészet, 2015)
Since the start of the civil war in Syria several major demographic shifts have taken place in the region. Syrian families are becoming members of ethnic minority groups in Jordan and Lebanon. The study shows that the influx of refugees is affecting the age structure, population rate, and the socio-economic structure of the communities. It is also affecting the sectarian and religious balance in Lebanon. The study also reveals that despite all the activities conducted by the international community to support the refugees in the region they lack the different dimensions of human security. The article examines how the demographic change in the host countries along with the lack of human security of the refugees could affect the national security in the host countries.